Asymptotic distributions of the number of restricted cycles in a random permutation - Kargina , Tatjana (Lietuvos matematikos rinkinys, 2009)
The value distribution of additive functions defined on the symmetric group with respect to the Ewens probability is examined. For the number of cycles with restricted lengths, we establish necessary and sufficient conditions under which the distributions converge weakly to a limit law.